Experimental investigation of heat transfer in oscillating pipes - Gül, Hasan; Evin, Duygu (My University, 2007)
In this study, characteristics of heat transfer and pressure loss of oscillating pipes at certain amplitudes and frequencies were investigated. For this aim, an oscillating mechanism was designed. Experiments were conducted for the oscillating frequency f, in the range of 0.008-1.988 Hz and dimensionless amplitude X=3, 6, 9. Reynolds number was changed from 5000 to 25000. It was determined that oscillating amplitude and frequency was reasonably effective on heat transfer and friction factor.
Ti?treşi?m yapan borularda isi transferi?ni?n deneysel olarak i?ncelenmesi?
Keywords: Heat transfer; Oscillation; Pulsating flow; Turbulent flow